2006
DOI: 10.1021/jm051039n
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of C-Glucoside Trisphosphates as myo-Inositol Trisphosphate Receptor Ligands. Synthesis of β-C-Glucoside Trisphosphates Based on the Conformational Restriction Strategy

Abstract: Beta-C-glucoside trisphosphates having a C2 side chain (3,7-anhydro-2-deoxy-D-glycero-D-gulo-octitol 1,5,6-trisphosphate, 11) and a C3 side chain (4,8-anhydro-2,3-dideoxy-D-glycero-D-gulo-nonanitol 1,6,7-trisphosphate, 12) were designed as structurally simplified analogues of a potent D-myo-inositol 1,4,5-trisphosphate (IP3) receptor ligand, adenophostin A. Construction of the beta-C-glucosidic structure, which was the key to their synthesis, was achieved by two different methods based on the conformational re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
(73 reference statements)
0
20
0
Order By: Relevance
“…AdA, a fungal glyconucleotide metabolite (448), and its many analogs (1,23,51,102,290,388,397,398,420,444,465) were discovered as agonists of the InsP 3 R. Although their molecular structures are significantly different from those of InsP 3 and its analogs (198), they activate the channel by interacting with the InsP 3 binding site (157). AdA binds InsP 3 R with substantially higher affinity and is significantly more potent in stimulating InsP 3 Rmediated Ca 2ϩ release than its natural agonist InsP 3 .…”
Section: H Activation Of Insp 3 R Channel By Adenophostin and Its Anmentioning
confidence: 99%
“…AdA, a fungal glyconucleotide metabolite (448), and its many analogs (1,23,51,102,290,388,397,398,420,444,465) were discovered as agonists of the InsP 3 R. Although their molecular structures are significantly different from those of InsP 3 and its analogs (198), they activate the channel by interacting with the InsP 3 binding site (157). AdA binds InsP 3 R with substantially higher affinity and is significantly more potent in stimulating InsP 3 Rmediated Ca 2ϩ release than its natural agonist InsP 3 .…”
Section: H Activation Of Insp 3 R Channel By Adenophostin and Its Anmentioning
confidence: 99%
“…The next step, entailing the reduction of ethyl C -aryl glycoside 9 , was also optimized. In general, the reduction of tetra-O-protected methyl C -aryl glycosides to the corresponding β- C -aryl glycosides with a Lewis acid and silane proceeds with high diastereoselectivity. Wang et al found that tetra-O-unprotected methyl C -aryl glycosides could be successfully reduced using AlCl 3 or BF 3 ·Et 2 O and Et 3 SiH with very high diastereoselectivity (β:α > 99:1) . Therefore, the direct reduction of tetra-O-unprotected ethyl C -aryl glycoside 9 was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…191 Recently, numerous analogs, including C-glycosides (such as 55) and compounds modified at the nucleotide backbone (such as 56), have been designed, synthesized and evaluated by Potter and co-workers to enhance InsP 3 R binding and elucidate the details of the interaction. [192][193][194][195][196][197] Since the InsP 3 receptors contain multiple binding domains (see Fig. 3), another strategy for enhancing binding has involved the development of tethered dimeric InsP 3 derivatives.…”
Section: Synthesis Of Natural Products For Elucidation Of Structure A...mentioning
confidence: 99%